Potensi Pengembangan Ekowisata Berbasis Masyarakat Pada Kawasan Curug Pamipiran Desa Tanjungsari Kecamatan Sadananya Kabupaten Tasikmalaya - Luthfi Ariel Setiawan; Rama Rizkya Rahman Prasyam; Nurmeina Haznabila; Siti Fadjarajani; Cahya Darmawan (Indonesian Journal of Glasial Geography, 2025)
This study examines the potential for developing community-based ecotourism in the Curug Pamipiran area, Tanjungsari Village, Sadananya District, Ciamis Regency. The main issue is the underutilization of natural tourism potential in a participatory and sustainable manner. The study aims to identify potentials, challenges, and formulate ecotourism development strategies involving active community participation. A descriptive qualitative approach was used, employing field observation and in-depth interviews with local leaders, village authorities, tourism actors, and visitors. Informants were selected purposively. Data were analyzed using the Miles and Huberman interactive model. Results indicate that Curug Pamipiran offers high natural and cultural appeal, with strong community interest in participating in tourism management. However, challenges include limited institutional capacity, poor infrastructure, and weak digital promotion. The study recommends establishing tourism awareness groups, providing tourism management training, and integrating ecotourism into village planning documents. With support from government and strategic partners, the area has strong potential to become a leading ecotourism destination based on conservation and community empowerment.